KAJIAN TERJEMAHAN AL-QURAN (Studi Tarjamah al-Quran Basa Jawi Assalam Karya Abu Taufiq S.) - Indrati, Anisah (MAGHZA, 2016)
This article examines the translation of the Koran in the Java language with title Kitab al-Qur'an Tarjamah Basa Jawi "Assalaam" by H. Abu Taufiq S. The focus of study in this article is to disclose the background and motivation of the writing of Tarjamah Qur 'an Basa Jawi "Assalaam", revealing the methods used and analyze the advantages and disadvantages of the Book Tarjamah Qur'an Basa Jawi "Assalaam". In addition this article also reveals the community's response to the study of the Koran in the Book Tarjamah Qur'an Basa Jawi "Assalaam". The analysis of the conclusions in the can are: First, the background and motivation of writing / preparation of the book of the Qur'an Tarjamah Basa Jawi "Assalaam", in addition to the need for further efforts of the grounding of the Koran is based on impulse some Quran verses. In addition, the Book Tarjamah Qur'an Basa Jawi "Assalaam" was also inspired by the many customers Jum'ah Khutbah book series. Second, the preparation method is the translation of the book according to the methods specified scholars associated with the rules of interpretation as well as relevant rules that must be obeyed. Third, while the excess is technically a book has been systematically arranged, so as to facilitate the reading and searching the desired passages, the translation has been through the process of interpretation, referring to the various books of tafsir, making it easier for readers to understand the biological paragraph. While the drawbacks is that unfortunate book Tarjamah Qur'an Basa Jawi "Assalaam" has not been evenly distributed, the new focus on the region of Central Java and Yogyakarta, designations in the form of volumes according to juz-Juz sometimes cut relationship between the verse being translated. Then the functional advantages is that for the Javanese in particular, Tarjamah Qur'an Basa Jawi "Assalaam" become an important reference in the framework of the Islamic propaganda, which is close to the psychological and cultural basis. Fourth, since the release, the book Tarjamah Qur'an Basa Jawi "Assalaam" is a demand and a boost by the various parties, both from the congregation culturally and ulema officially through the government. It is not surprising presence responded very positively by the public.